1988
DOI: 10.1007/bf03020347
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of epidural morphine-induced respiratory depression and pruritus with nalbuphine

Abstract: Epidural morphine has become accepted as an efficient means of postoperative pain management. However, the problem of delayed respiratory depression has restricted its use, and in most centres patients are monitored for 24 hours following the last dose of epidural morphine, in an intensive care setting. Naloxone has been found to reverse this respiratory depression ~ but there are reported problems with reversal of analgesia. 2 Many investigators now believe naloxone to have significant effects on cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…With regard to human subjects, itch is the common side effect of epidural and intrathecal injections of morphine (for review, see ref. 30), and itch induced by epidural morphine is inhibited by naloxone and opioid receptor antagonist (31,32). Thus, it is possible that opioid antagonists act on the central nervous system to inhibit itching in human subjects and itch-associated response in mice.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to human subjects, itch is the common side effect of epidural and intrathecal injections of morphine (for review, see ref. 30), and itch induced by epidural morphine is inhibited by naloxone and opioid receptor antagonist (31,32). Thus, it is possible that opioid antagonists act on the central nervous system to inhibit itching in human subjects and itch-associated response in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not an HDU can alter this is impossible to know and, in any case, some patients are deliberately discharged to permit a more natural terminal stage. However, it would seem that there must be room for improvement in the expected to live group [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not an HDU can alter this is impossible to know and, in any case, some patients are deliberately discharged to permit a more natural terminal stage. However, it would seem that there must be room for improvement in the expected to live group [14,15].Compared to an ICU the costs after initial outlay are likely to be modest [16] but as the demand increases these will rise [4]. The major cost is in nursing provision and it is difficult to match nurse staffing with bed occupancy although the high usage for elective surgery may make this more predictable than ICU staffing.…”
mentioning
confidence: 99%
“…14 In children, however, nalbuphine has been shown to increase drowsiness 14,17 and is ineffective in treating pruritus. 19 Droperidol has been found to decrease the incidence of pruritus, but it also increases somnolence relative to placebo.…”
Section: Introductionmentioning
confidence: 99%
“…10 Most existing therapeutic approaches to treatment of opioid-induced pruritus are unreliable, are often ineffective, and may increase the risk of adverse drug reactions. [12][13][14] For example, naltrexone was more effective than placebo in reducing the incidence of pruritus (reduction of 34% to 62%), but this drug also decreases analgesia. 15,16 Studies of nalbuphine in adults have generated conflicting data: some studies reported no reduction in pruritus, 13,17 whereas others showed a lower incidence of pruritus with nalbuphine than with placebo (13% versus 78%, respectively) 18 and lower pruritus scores (by 1 to 2 points on a 4-point scale).…”
Section: Introductionmentioning
confidence: 99%